Tissue factor mRNA in THP-1 monocytic cells is regulated at both transcriptional and posttranscriptional levels in response to lipopolysaccharide. - Brand, K (1991)
Tissue factor (TF) is transiently expressed in human monocytes exposed to the inflammatory agonist bacterial lipopolysaccharide (LPS). Since TF is the major cellular initiator of the coagulation protease cascades, it is inferred that its expression within the vasculature is strictly regulated. In this study, we investigated mechanisms which control TF mRNA expression in the human monocytic cell line THP-1. LPS induced a rapid and transient accumulation of the mature 2.2-kb TF mRNA, which was maximal at 2 h. After stimulation, the rate of transcription of the TF gene was increased (3.3 +/- 1.3)fold. In addition, we observed a significant change in TF mRNA stability: at 1 h after LPS stimulation, TF mRNA was stable during a 60-min period and had a half-life of greater than 120 min, whereas at 2 h, the half-life had declined to 25 +/- 5 min. Furthermore, a larger (3.4-kb) TF RNA species was induced in these cells; the size of this species and data from selective hybridizations with intron-specific probes are consistent with the presence of an unspliced copy of intron 1. These results demonstrate that the LPS-induced accumulation of TF mRNA levels in these monocytic cells is accomplished by both transcriptional and posttranscriptional control mechanisms.